The Analysis of Anemia Prevention Model in Pregnant Women in Banten - Rukmaini; Nur Indrawaty Lipoeto; Masrul; Nursyirwan Effendi (Journal of Pharmacy and Nutrition Sciences, 2019)
Anemia among pregnant women, especially in developing countries is still becoming problematic. Although several programs implemented, they showed a modest impact on the reduction. It is essential to develop the efficient approach for tackling this problem. This study was aimed to identify and develop the model of anemia associated modality care that can be used for preventing and managing of anemia during pregnancy. This research was a cross-sectional study of creating a prevention model using Structural Equation Modeling (SEM PLS) technique. This technique was to find out which indicator variables has the direct and indirect influence of causing anemic pregnant women. This research was conducted in the Kaduhejo, Pandeglang, Banten in 2018 and involved 258 pregnant women living with their families. These respondents were recruited using multistage cluster sampling. Data collection was conducted by a questionnaire to identify the pregnant women characteristics and maternal knowledge, attitudes, perceptions, and family support. The models were constructed to arrange the intervention module as well as analyzing model using SEM-PLS. The results of this study showed that exogenous variables had a statistically significant T value reflected on the variable> 1.96, thus indicating that the indicator block had a positive and significant effect of reflecting the variable. In conclusion, anemia among pregnant women influenced by direct factors, such as family support, maternal knowledge and perception.